Severity of Sleep Bruxism and its Implications for the Stomatognathic System in Healthy Subjects - Palinkas, Marcelo; Marin, Natália Yanota; Bataglion, César; Corrêa de Mello, Edneia; De Luca Canto, Graziela; Maria Napolitano Gonçalves, Ligia; Hirono Hotta, Takami; Hallak Regalo, Isabela; Eduardo Cecilio Hallak, Jaime; Siéssere, Selma; Cecilio Hallak Regalo, Simone (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Sleep bruxism (SB) changes the functionality patterns of the stomatognathic system. However, its severity can be an aggravating factor in the function of this complex system. AIM: The purpose of the study was to investigate the stomatognathic system of healthy subjects with different severity of SB, as determined by BiteStrip. METHODS: Thirty-four subjects were divided into two groups: Mild SB (n = 15) and severe SB (n = 19). Electromyograph was used to evaluate the electromyographic activity of the right masseter (RM), left masseter (LM), right temporal (RT), and left temporal (LT) muscles at mandibular rest, right and left laterality, protrusion, and maximum voluntary contraction. Molar bite force was measured by the dynamometer. The data were tabulated and submitted for statistical analysis (p < 0.05). RESULTS: Molar bite force was significantly lower in the severe SB group. There was a significant increase in electromyographic activity in the severe SB group for the mandibular rest tasks (RM, RT, and LT), protrusion (RM, LM, RT, and LT), and right and left laterality in the temporalis muscles. There was a significant decrease in electromyographic activity in the severe SB group in maximum voluntary contraction for the masseter and temporalis muscles. CONCLUSION: Subjects with severe SB demonstrated greater functional impairment of the stomatognathic system, mainly affecting the electromyographic activity and molar bite force.